The African American experience : psychoanalytic perspectives - Akhtar, Salman, 1946 July 31- (Jason Aronson, 2012)
The African American Experience: Psychoanalytic Perspectives edited by Salman Akhtar brings together the contributions of distinguished mental health professionals and scholars of humanities to offer a multifaceted perspective on the transgenerational trauma of slavery, the hardship of single parent families, the ruthlessness of anti-black racism, and the crushing burden of poverty and social disenfranchisement on the African American individual. The book also sheds light on the resilience of spirit, the dignity of perseverance, and the glow of talent that is widespread in this group. It contains penetrating and informative biographical essays on Martin Luther King, Jr., Malcolm X, Mohammad Ali, Barack Obama, and Oprah Winfrey. Such discourse on human greatness is balanced by the considerations of daily joy and anguish on clinical and societal levels. This wide-ranging and nuanced volume on the history, culture, and psychosocial struggles of African American people fills an important gap in the literature on psychotherapy and psychoanalysis.